2019
DOI: 10.1038/s41422-019-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 modulates Parkinson’s disease LRRK2 kinase activity through allosteric regulation and confers neuroprotection

Abstract: Missense mutations in Leucine-Rich Repeat Kinase 2 (LRRK2) cause the majority of familial and some sporadic forms of Parkinson's disease (PD). The hyperactivity of LRRK2 kinase induced by the pathogenic mutations underlies neurotoxicity, promoting the development of LRRK2 kinase inhibitors as therapeutics. Many potent and specific small-molecule LRRK2 inhibitors have been reported with promise. However, nearly all inhibitors are ATP competitive-some with unwanted side effects and unclear clinical outcome-alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 98 publications
(166 reference statements)
2
45
0
Order By: Relevance
“…We also note the recent report that vitamin B 12 is a ‘mixed-type allosteric inhibitor’ of LRRK2 kinase activity; that is, vitamin B 12 does not compete with ATP for the active site of the LRRK2 kinase domain, as is the case for all other LRRK2 kinase inhibitors, but binds elsewhere to induce a conformational change [216]. Fascinatingly, vitamin B 12 appears to promote the monomerisation of LRRK2, opening the door to an alternative therapeutic approach.…”
Section: Discussionmentioning
confidence: 94%
“…We also note the recent report that vitamin B 12 is a ‘mixed-type allosteric inhibitor’ of LRRK2 kinase activity; that is, vitamin B 12 does not compete with ATP for the active site of the LRRK2 kinase domain, as is the case for all other LRRK2 kinase inhibitors, but binds elsewhere to induce a conformational change [216]. Fascinatingly, vitamin B 12 appears to promote the monomerisation of LRRK2, opening the door to an alternative therapeutic approach.…”
Section: Discussionmentioning
confidence: 94%
“…Through a promising breakthrough reported in a recent paper in Cell Research by Schaffner et al, 3 the roadblock resulting from the unacceptably high risk:benefit ratio of existing LRRK2 inhibitors may now be circumvented. This group has used a high-throughput screen of a small library of 2080 FDA-approved compounds to identify a naturally occurring and potent compound that directly binds LRRK2, altering the conformation of the protein and interfering with ATP binding, thus allosterically inhibiting its kinase activity.…”
mentioning
confidence: 99%
“…While aggregation of specific proteins (α-synuclein and β-amyloid) are defining characteristics PD and AD pathology, the role of these proteins in the early pathogenesis of the sporadic forms of these disorders is not clear and has led some to hypothesize that insight into disease modifying targets requires discovery of other biomarkers present at disease onset and subsequent subgroup analysis according to these candidate biomarkers [22,23]. Data from this study, showing that B12 levels are lower in PD than other neurodegenerative diseases, along with recent clinical [7] and biochemical data [17] suggest that B12 warrants further study as an early PD biomarker.…”
Section: Discussionmentioning
confidence: 67%
“…This observation raises the question as to whether B12 levels might have a more direct effect on PD progression. Interestingly, Schaffner and colleagues recently reported that B12 directly modulates leucine-rich repeat kinase 2 (LRRK2) [17]. Mutations in LRRK2 account for about 5% of hereditary PD [18] and the most common variant (G2019S) has been established to increase LRRK2 activity [19,20].…”
Section: Discussionmentioning
confidence: 99%